Ptyalism in pregnancy – a review of epidemiology and practices. (March 2016) - Thaxter Nesbeth, Karen A.; Samuels, Leslie A.; Nicholson Daley, Carla; Gossell-Williams, Maxine; Nesbeth, Damian A.
Abstract: Ptyalism gravidarum is an oral pathological condition specific to gravidity. We present a review of the literature regarding epidemiology internationally, and then highlight therapies reported by patients and caregivers. This often distressing repeated filling of the mouth with watery saliva in a pregnant patient was previously exclusively associated with hyperemesis gravidarum, and the consequent maternal-fetal risk. Our dissertation includes reference to a rare case of isolated sialorrhoea of pregnancy, without nausea or emesis. Both pharmacological and homoeopathic therapies are discussed, and inherent risks to mother and infant are highlighted. It is strongly recommended that this condition be given attention in antenatal care settings, to optimize short, middle and long term pregnancy outcomes.